Attachment Anxiety and Internalized Misogyny as Predictors of Relationship Instability in Young Women - Karstensen, Valerie; Novak, Mateja (Psychology of Woman Journal, 2024)
Objective: This study aimed to investigate how attachment anxiety and internalized misogyny predict relationship instability among young women.Methods and Materials: A correlational descriptive design was employed with 460 female participants from Slovenia, aged 18 to 30. Standardized self-report measures were utilized to assess relationship instability (dependent variable), attachment anxiety, and internalized misogyny (independent variables). Data were analyzed using IBM SPSS Statistics version 27, focusing on Pearson correlation to explore bivariate associations and multiple linear regression to determine the combined predictive value of attachment anxiety and internalized misogyny on relationship instability. All participants provided informed consent prior to their inclusion, and anonymity was ensured throughout the study.Findings: Pearson correlation analyses indicated that both attachment anxiety and internalized misogyny were significantly and positively associated with relationship instability (p < .001). Multiple linear regression analysis further revealed that attachment anxiety emerged as the stronger predictor (β = .54, p < .001), although internalized misogyny also made a significant contribution (β = .31, p < .001). The overall model was statistically significant, F(2, 457) = 194.35, p < .001, explaining approximately 46% of the variance in relationship instability (R² = .46, adjusted R² = .45). These results highlight the importance of both psychosocial and ideological factors in predicting instability in young women’s romantic relationships.Conclusion: Attachment anxiety and internalized misogyny significantly contribute to relationship instability, reinforcing the need to address not only individual emotional vulnerabilities but also internalized gender biases when supporting young women in romantic contexts. Interventions targeting the reduction of attachment-related fears and challenging harmful beliefs about women may promote more stable and satisfying romantic partnerships.